PENGARUH KEPEMILIKAN INSTITUSIONAL, EFEKTIVITAS KOMITE AUDIT DAN KOMPLEKSITAS AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN BARANG KONSUMEN NON-PRIMER SUB SEKTOR JASA KONSUMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2021 – 2023) - Putri Khairani; Andreas Andreas; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study aims to examine the effect of institutional ownership, audit committee size,audit committee meeting frequency, and audit complexity on the timeliness of financialreporting in consumer service companies listed on the Indonesia Stock Exchange for theperiod 2021–2023. This research uses a quantitative approach with secondary dataobtained from companies financial statements. The sample was determined usingpurposive sampling, resulting in 93 observations. The data analysis method used islogistic regression with the assistance of SPSS version 26. The results show thatinstitutional ownership has a significant negative effect on the timeliness of financialreporting, while audit committee size, audit committee meeting frequency, and auditcomplexity have no significant effect. This study is expected to contribute to thedevelopment of accounting knowledge and serve as a reference for relevant parties inimproving the timeliness of financial reporting. Keywords: Timeliness Of Financial Reporting, Institutional Ownership, Audit CommitteeSize, Audit Committee Meeting Frequency, Audit Complexity